應用於電子元件之奈米材料在臨場穿透式電子顯微鏡下電與熱傳輸行為之研究 - 吳文偉; Wu Wen-Wei (My University, 2013)
隨科技的進展，各類材料的使用已趨小型化。在這個趨勢下，原子尺度之結構與動 力學對材料性質的影響越來越重要，材料初始形成的情形已決定一切。未來材料的發展 將遂步整合不同材料的特性，以發展出特殊性能的新穎材料。以原子為整合的基本單位 是不可避免的趨勢。因此原子層表面的型態、不同原子層界面熱力學、界面缺陷等的了 解都將是達成此目標之重要因素。因此近年來很多先進的研究已逐步往此方向進行，也 獲得了許多嶄新的結果。 目前原子尺度之結構與動力學的研究偏向理論的領域，並不見得與實際所應用的材 料系統相連結，因此探討實際應用材料系統的原子尺度之結構與動力學也將是非常重要 的課題。此課題不僅對學術上的提昇有助益，並且可以改進製造技術。原子移動與材料 科學中基本現象如擴散、相變化動力學、缺陷生成有密切關係，也與熱、電等物理特性 息息相關。 In situ UHV – TEM 具有原子鑑別率、由於穿透電子特性，可觀察對埋覆界面變 化，許多缺陷，如界面差排，可顯現清楚對比，而近期，利用此一設備，本研究團隊 亦在此領域發表幾項重要研究成果，也累積許多優異的研究成果，並發表在國際知名 頂尖期刊，在世界上居於領先的地位，並且持續往更深入與重要的主題進行研究。 本研究計畫以當前受重視的電子元件之材料作為研究對象，分五子題，為期三年 進行，各子題間相互關聯，也分別有先前研究所累積的基礎、經驗與初步成果，相信 很多研究都能在期間內很有效率地做出好的結果，以期能對學術方面的理論研究更為 透徹，並對產業的製程及應用上帶來更多的彈性。以下分別列舉五個主題之相關內容。 1. 奈米雙晶結構對於銅導線電遷移影響之研究 2. 金屬矽化物奈米線之成長動力學研究 3. 奈米線之電子傳輸現象與結構研究 4.電阻式記憶體之電子傳輸現象與結構研究 5.相變化奈米線之固態擴散反應動力學研究及特性量測

In situ study of the temperature and current induced phase transformation, structural and chemical evolution of nanocrystals is important for understanding the structure and stability of nanomaterials. Transmission electron microscopy (TEM), one of the most powerful tools for characterizing nanostructure materials, is essential for nanotechnology. Combining the above two features and advantages, in situ TEM is a technique that allows a direct observation of dynamic properties in nanoscale. Recent development of UHV-TEM further enables the investigation on atomic-scale materials systems in a clean environment. The appropriate utilization of the UHV-TEM will be beneficial in studying the fundamental mechanisms of dynamic reactions, formation of transient phase, solid-state amorphization, epitaxial growth, growth kinetics and evolution of defects. In this paper, we present the most recent progress in observing dynamic processes in nanoscale by in situ UHV-TEM. Low-dimensional building blocks, such as nanodots, nanowires and nanotubes, are especially attractive candidates for developing a bottom-up paradigm for nanotechnology-enabled architectures. Zero-dimensional nanocrystals have been a subject of intense study. The nanodots exhibit unique physical properties owing to the small size and quantum effects. The dynamical change of nanodots during growth is not only of interest itself; it may also provide key understanding for the thin film growth. On the other hand, metallic nanowires and nanotubes can both act as interconnects for the transport of charge carriers as well as active device elements. Semiconductor nanowires offer all the properties of traditional semiconductors, such as excellent control of the electrical and optical properties, as well as new benefits including possible carrier mobility enhancements for less scattering attributed to reduction in dimension. A wide variety of nanowires can be synthesized from group IV, III-V, and II-VI materials, and can be exploited to make myriad nanoscale devices, from transistors to light emitting diodes and biosensors. These developments suggest that nanowires are excellent candidates for bottom-up assembly of architecturally complex integrated devices system. As the critical dimensions for devices become smaller, it is necessary to precisely specify the crystal structures, interface morphology, shapes and sizes of individual features; also, control in atomic scale is essential. Achieving this level of control requires a detailed understanding of fundamental processes which occur during processing. State-of-the-art atomic-resolution instruments and techniques, such as UHV-TEM, VT-STM and atomic resolution TEM, will be utilized to investigate the structures and dynamic changes in several technologically important materials systems, such as Si-based nanowires and semiconducting oxide nanostructured materials. Through observation of thermal transport, electrical transport, phase change and/or growth in situ, we can understand their mechanisms and model relevant processes. The research will be conducted on the in situ UHV-TEM investigation of nanostructures. The emphases will be placed on the following topics, 1. Effect of nano-twin boundary on Cu electromigration. 2. Investigation on metal silicide nanowires and their growth kinetics. 3. Observation of electrical transport and structural evolution on nanowires by in situ TEM. 4. The electrical transport behavior and structural analysis of ReRAM. 5. In situ TEM measurement and solid state reaction of phase change materials
Investigation on the electrical and thermal transport properties of nanomaterials under in-situ TEM for electronic devices
Keywords: 臨場超高真空穿透式電子顯微鏡; 成長動力學; 電遷移; 低電阻率金屬矽化物; 奈米線; 異; in situ UHV-TEM; growth kinetics; electromigration; low-resistivity metal silicides; nanowires